Nexus Between Foreign Direct Investment Inflow, Renewable Energy Consumption, Ambient Air Pollution, and Human Mortality: A Public Health Perspective From Non-linear ARDL Approach - Muhammad Haroon Shah; Sultan Salem; Bilal Ahmed; Irfan Ullah; Alam Rehman; Muhammad Zeeshan; Zeeshan Fareed (Frontiers Media S.A., 2022)
A huge foreign direct investment (FDI) inflow has been witnessed in China, though on the one hand, it brings a significant contribution to economic growth. On the other hand, it adversely affects the ambient air pollution that may affect human mortality in the country. Renewable energy (RE) usage meets the country's energy needs with no adverse effect on the environment. Therefore, this study is trying to empirically analyze the effect of FDI inflow on human morality and RE consumption in China. We used time-series data for 1998-2020 and applied a non-linear ARDL approach for the estimations. The empirical outcomes suggest that FDI inflow positively affects mortality and RE. There is also unidirectional causality running from RE and pollution to mortality. In addition, the relationship among the variable verifies the existence of a non-linear relationship. The government needs policy guidelines to further boost FDI inflow due to its positive aspects. However, to reduce the negative effect on the environment and human morality, the extensive usage of RE should be adopted. Indeed, proper legislation for foreign firms might be a good step toward quality environmental and longevity of human health in society.